CALCULATION OF DEPOSIT INSURANCE SYSTEM USING VISUAL BASIC 6.0 DI PT. BNI LIFE INSURANCE - Riki Dimar Ardiansyah; Yuce Yuliani, Skom, MMsi (Jurnal Sistem Informasi, 2004)
PT. BNI Life Insurance, a joint force between the PT Bank Negara Indonesia(Persero) Tbk as a national financial institution with PT BNI Life Insurance (Persero)as an institution that has long experienced in processing insurance fund.Scientific writing is about a system created to help solve the problem about thecalculation of deposit insurance and the application that is easy to follow or becombined by each employee in that company.This application is done using Data Flow Diagrams (DFD) as a tool, Database designusing Entity Relationship Diagram concept (ERD) and the concept of normalization.The programming language used is by using Microsoft Visual Basic 6.0